Plant diversity improves resistance of plant biomass and soil microbial communities to drought. (5th May 2022) - Li, Yan; Wang, Jiang; Shen, Congcong; Wang, Jichen; Singh, Brajesh K.; Ge, Yuan
Abstract: Biodiversity is known to affect ecosystem resistance and have implications for the maintenance of ecosystem functions and services under climate change. Compared to numbers of studies focusing on above‐ground vegetation, the response of below‐ground communities to abiotic stresses along plant diversity gradients is often ignored and is considered an important knowledge gap in ecosystem ecology. Here we conducted an integrative research to evaluate the resistance of plant biomass, and soil microbial communities and associated functional profiles to drought under varying plant diversity. We carried out a 3‐year manipulation experiment by factorially controlling plant diversity gradient (1, 2, 4 and 8 species richness) and soil moisture treatment (drought and non‐drought), and investigated the responses of plant biomass, soil bacterial and fungal diversity and community composition, soil glomalin, and five key soil enzymes. We found that plant diversity significantly improved the resistance of soil fungal communities and microbial functional profiles characterized by soil glomalin and five key enzymes, which was partly driven by the availability and accessibility of soil resources (e.g. soil moisture and organic matter) mediated by plant diversity. Furthermore, our results indicated that the enhanced resistance of fungal communities was consistent with ecological insurance theory that diverse fungal communities at high plant diversity had a higher probability of containing taxa that adapt to drought. Synthesis . Our study provides novel empirical insights into the mechanism underlying the regulatory effect of plant diversity on resistance of above‐ground vegetation and below‐ground biota to drought, with implications for understanding ecosystem response to climate change and improving biodiversity conservation practices. Abstract : Our study provides novel empirical insights into the mechanism underlying the regulatory effect of plant diversity on resistance of above‐ground vegetation and below‐ground biota to drought, with implications for understanding ecosystem response to climate change and improving biodiversity conservation practices.